Physiological and Biochemical Mechanisms of Seed Priming-Induced Chilling Tolerance in Rice Cultivars - Hussain, Saddam; Khan, Fahad; Hussain, Hafiz A.; Nie, Lixiao (Frontiers in Plant Science, 2016)
Rice belongs to tropical and subtropical environments and is extremely sensitive to chilling stress particularly during emergence and early stages of seedling development. Seed priming can be a good approach to enhance rice germination and stand establishment under chilling stress. The present study examined the role of different seed priming techniques viz., hydropriming, osmopriming, redox priming, chemical priming, and hormonal priming, in enhancing the chilling tolerance in rice. The most effective reagents and their pre-optimized concentrations based on preliminary experiments were used in this study. Two different rice cultivars were sown under chilling stress (18˚C) and normal temperatures (28˚C) in separate growth chambers. A non-primed control treatment was also maintained for comparison. Chilling stress caused erratic and delayed germination, poor seedling growth, reduced starch metabolism and lower respiration rate, while higher lipid peroxidation and hydrogen peroxide accumulation in rice seedlings of both cultivars. Nevertheless, all the seed priming treatments effectively alleviated the negative effects of chilling stress. In addition, seed priming treatments triggered the activities of superoxide dismutase, peroxidase, and catalase, and enhanced the accumulations of glutathione and free proline in rice seedlings, which suggests that these measures help prevent the rice seedlings from chilling induced oxidative stress. Chemical priming with selenium and hormonal priming with salicylic acid remained more effective treatments for both rice cultivars under chilling stress than all other priming treatments. The better performance and greater tolerance of primed rice seedlings was associated with enhanced starch metabolism, high respiration rate, lower lipid peroxidation, and strong antioxidative defense system under chilling stress.